Social and Economic Impact of Sahaja Samrudha on Sustainable Agriculture in Karnataka - Roshni Yeshawanth; Prashanth Kumar; Ravikantha Prabhu (Journal of Social Entrepreneurship Theory and Practice, 2025)
This study investigates the role of Sahaja Samrudha, a social enterprise based in Karnataka, in encouraging sustainable agriculture and community development through a mixed-methods approach involving a survey of 62 custodian farmers. While demographic data such as age, gender, and education were collected, the primary focus was on assessing the broader social and economic impacts of the enterprise. The outcomes highlight Sahaja Samrudha’s significant contributions to environmental sustainability, income enhancement, and the empowerment of marginalised groups, particularly women, through training and capacity-building initiatives. Despite these positive outcomes, the study identifies areas for development, notably in access to social services and education. Although the regional scope may limit broader applicability, the research provides valuable insights into the transformative potential of eco-social enterprises in advancing inclusive growth and sustainable development, emphasising the importance of supportive policies and resource allocation to amplify their impact across diverse contexts.